👤

A = 3 (x − 2)(x + 5)
C = (2 - x2)(3+x)
B=-2(x + 3) (2x - 4)
D=2(x – 3)2
A=(x + 1)(x – 4)+ (x + 3)(x - 1)
B=(x + 1)2 – (x + 3)(x - 5)


Répondre :

Réponse :

A = 3(x-2)(x+5) = 3(x²+ 5 x - 2 x - 10) = 3(x²+ 3 x - 10) = 3 x² + 9 x - 30

B = - 2(x+3)(2 x - 4) = - 2(2 x² - 4 x + 6 x - 12) = - 2(2 x² + 2 x - 12)

   = - 4 x² - 4 x + 24

C = (2 - x²)(3 + x) = 6 + 2 x - 3 x² - x³ = - x³ - 3 x² + 2 x + 6

D = 2(x-3)² = 2(x²-6 x + 9) = 2 x² - 12 x + 18

A = (x+1)(x-4) + (x+3)(x-1)

   = x² - 3 x - 4 + x² + 2 x - 3

   = 2 x² - x - 7

B = (x+1)² - (x +3)(x-5)

  = x²+2 x +1 -(x²- 2 x - 15)

  =  x²+2 x +1 -x²+ 2 x + 15

  = 4 x + 16  

Explications étape par étape

Réponse :

(a + b) (c + d) = ac + ad  +bc +bd puis on simplifie.

(a+b)² = a² +2ab +b²

(a-b)² = a² - 2ab +b²

Explications étape par étape

A = 3 (x − 2)(x + 5) = 3 *(x² +5x  - 2x -10) = 3 *(x² +3x -10) = 3x² +9x -30

C = (2 - x²)(3+x) = 6 + 2x  -3x² -x³ = -x³-3x² + 2x+ 6

B=-2(x + 3) (2x - 4) = -2(2x²-4x+6x-12) = -2(2x²+2x-12) = -4x² -4x +24

D=2(x – 3)² = 2(x-3)(x-3) = 2(x² -6x +9) = 2x² -12x +18

A=(x + 1)(x – 4)+ (x + 3)(x - 1) = x² -4x +x -4  +   x²-x +3x -3 = 2x² -x -7

B=(x + 1)² – (x + 3)(x - 5) = x²+2x +1  -( x²-5x +3x -15) =x²+2x +1  -x² + 5x - 3x  +15

= 4x +16